Effectiveness of sugar taxation policies in Asia and Africa: a systematic review - Fernandes, Miyola Cia; Jodalli, Praveen S.; Saeed, Deema Waleed; Gaunkar, Ridhima; Almalki, Sultan; Gowdar, Inderjit; Nagarsekar, Aradhana (Frontiers in Oral Health, 2025)
BackgroundThe prevalence of major noncommunicable diseases (NCDs) such as cardiovascular disease, cancer, and diabetes is rising rapidly in Asia and Africa. One of the major modifiable risk factors for these diseases is the consumption of free sugars, commonly found in sugary drinks. To address this issue, some countries have implemented food taxes such as taxes on sugar-sweetened beverages as part of national public health policies to reduce its intake. The review aims to assess the effects of national taxation of sugar-sweetened beverages within the continents of Asia and Africa.MethodsEight databases (MEDLINE (Ovid), Embase, PubMed, Cochrane, SCOPUS, Web of Science and ProQuest) were searched, and seven studies were included in this review. Only studies focused on the taxation of SSBs in Asia and Africa until 30 June 2023 and those that studied the impact of national sugar taxation among their population were included. Simulation or studies evaluating the estimation effect of taxes were excluded. All eligible records were assessed for the risk of bias using the NIH Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies, and the certainty of the evidence was reviewed.ResultsSeven studies included in this review investigated the impact of sugar tax policies in South Africa, India, Thailand, and Saudi Arabia. The interventions in these countries were implemented from 2017 to 2018 mainly for sugar-sweetened beverages. The studies provided evidence on changes in the volume of purchase, consumption, and sugar content of taxed items. Some evidence was found to suggest the positive impact of SSB taxes in reducing consumption of taxed items which ranged from 2.5% to 19% decrease. However, no study has reported on individual health outcomes.ConclusionThere is substantial evidence of a decrease in the consumption of taxed items, but there is uncertainty about the health impact of these outcomes. Future research should prioritize longitudinal studies assessing direct health impacts of SSB taxation policies. Additionally, generalizability of the results of such fiscal policies need to be investigated in lower economic settings and thus be of significance for uniform health policy reforms.Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/view/CRD42023427030, PROSPERO (CRD42023427030).